Escape from Camp 14 : one man's remarkable odyssey from North Korea to freedom in the West - Harden, Blaine. (Viking, 2012)
Twenty-six years ago, Shin Dong-hyuk was born inside Camp 14, one of five sprawling political prisons in the mountains of North Korea. This is the gripping, terrifying story of his escape from this no-exit prison-- to freedom in South Korea.